Isolation of a bis(imino)pyridine molybdenum(i) iodide complex through controlled reduction and interconversion of its reaction products. Issue 24 (20th April 2016) - Pal, Raja; Cherry, Brian R.; Flores, Marco; Groy, Thomas L.; Trovitch, Ryan J.
Abstract : This effort describes the isolation of a persistent Mo(i ) monoiodide complex and its conversion to an unusual set of divalent (PDI)Mo complexes. Abstract : Analysis of previously reported [( Ph2PPr PDI)MoI][I] by cyclic voltammetry revealed a reversible wave at −1.20 V vs. Fc +/0, corresponding to the Mo(ii )/Mo(i ) redox couple. Reduction of [( Ph2PPr PDI)MoI][I] using stoichiometric K/naphthalene resulted in ligand deprotonation rather than reduction to yield a Mo(ii ) monoiodide complex featuring a Mo–C bond to the α-position of one imine substituent, (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoI. Successful isolation of the inner-sphere Mo(i ) monoiodide complex, ( Ph2PPr PDI)MoI, was achieved via reduction of [( Ph2PPr PDI)MoI][I] with equimolar Na/naphthalene. This complex was found to have a near octahedral coordination geometry by single crystal X-ray diffraction and electron paramagnetic resonance (EPR) spectroscopy revealed an unpaired Mo-based electron which is highly delocalized onto the PDI chelate core. Attempts to prepare a Mo(i ) monohydride complex upon adding NaEt3 BH to ( Ph2PPr PDI)MoI resulted in disproportionation to yield an equimolar quantity of (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoH and newly identified ( Ph2PPr PDI)MoH2 . Independent preparation of ( Ph2PPr PDI)MoH2 was achieved by adding 2 equiv. NaEt3 BH to [( Ph2PPr PDI)MoI][I] and a minimum hydride resonance T 1 of 176 ms suggests that the Mo-bound H atoms are best described as classical hydrides. Interestingly, ( Ph2PPr PDI)MoH2 can be converted to (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoI upon iodomethane addition, while ( Ph2PPr PDI)MoH2 is prepared from (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoI in the presence of excess NaEt3 BH. Similarly, (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoI can be converted to (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoH with 1 equiv. of NaEt3 BH, while the opposite transformation occurs following iodomethane addition to (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoH. Facile interconversion between [( Ph2PPr PDI)MoI][I], (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoI, (κ 6 - P, N, N, N, C, P - Ph2PPr PDI)MoH, and ( Ph2PPr PDI)MoH2 is expected to guide future reactivity studies on this unique set of compounds.